A consideration of the paradigm of exercise physiology - Kilgore, J. L.; Baker, J. S.; Davies, B. (Research in Sports Medicine, 2014)
Exercise physiology, in terms of the history of biological sciences, is quite young and has a rather tumultuous history - as it spans physical education, health & medicine, sport science, and biology. This has led to the development of differing definitions, research approaches, practices and goals. This is easily seen in the presence of competing and non-universally adopted definitions of fitness. Such internal inconsistencies portray to the outside world a discipline experiencing the problems associated with a changing paradigm. Every science requires the presence of a paradigm that both describes and guides the evolution of thinking, experimentation, and the application of such. It is argued here that exercise physiology has been operating without benefit of a satisfactory and relevant paradigm. A further proposition is that the required disciplinary definitions derived from an articulated paradigm are also absent. A paradigmatic scheme based on biological dogma is presented along with proposed definitions.